Jalur trem Modjoagoeng-Ngoro: pendapatan dan pengaruhnya bagi masyarakat Jombang tahun 1890-1900 - Dimas Bagus Aditya (Universitas Negeri Malang, 2023)
The Modjoagoeng-Ngoro tramway is a branch of the Mojokerto-Gemekan-Ngoro tramway. The Oost-Java Stoomtram Maatschappij railway line with the Mojoagung-Ngoro segment is used to transport plantation products at several sugar factories connected to this line, such as the Soekodhono Sugar Factory, Seloredjo Sugar Factory, and Ngoro Sugar Factory. The construction of the Mojoagung-Ngoro railway has an impact on the lives of the people of Jombang so that a small market is formed near the station stop. This paper aims to describe the Modjoagoeng-Ngoro tramline which includes the history of the establishment of the OJS tramline in Surabaya Regency, including Mojoagung-Ngoro line, the income earned by the OJS line in the Modjoagoeng-Ngoro segment, and the effects caused by the establishment of the OJS line. The method used in this paper is the historical method which consist of heuristics, source critism, interpretation, and historiography. The results obtained in this study are the gross income obtained by the Oost-Java Stoomtram Maatschappij (OJS) company experiencing ups and downs in income. This reflects that the OJS line is highly dependent on the fluctuations in sugar and coffee production along this railway. The impact felt by the community due to the construction of the Modjoagoeng-Ngoro tramline is the formation of a small trading area around the OJS stop station. Jalur trem Modjoagoeng-Ngoro merupakan rangkaian cabang dari jalur trem Mojokerto-Gemekan-Ngoro. Jalur rel kereta api Oost-Java Stoomtram Maatschappij dengan segmen Mojoagung-Ngoro digunakan untuk mengangkut hasil perkebunan dibeberapa pabrik gula yang terhubung dengan jalur ini, seperti Pabrik Gula Soekodhono, Pabrik Gula Seloredjo, dan Pabrik Gula Ngoro. Pembangunan jalur rel Mojoagung-Ngoro berdampak terhadap kehidupan masyarakat Jombang sehingga terbentuk pasar kecil di dekat stasiun pemberhentian. Tulisan ini bertujuan untuk memaparkan mengenai jalur trem Modjoagoeng-Ngoro yang didalamnya mencakup sejarah pendirian jalur trem OJS di Karasidenan Surabaya termasuk jalur lintas Mojoagung-Ngoro, pendapatan yang diperoleh jalur OJS segmen Modjoagoeng-Ngoro, dan pengaruh yang ditimbulkan akibat didirikannya jalur OJS. Metode yang digunakan dalam penulisan ini adalah metode sejarah yang terdiri atas heuristik, kritik sumber, interpretasi, dan historiografi. Hasil yang didapatkan dalam penelitian ini adalah pendapatan bruto yang diperoleh oleh perusahaan Oost-Java Stoomtram Maatschappij (OJS) mengalami pasang surut pendapatan. Hal ini mencerminkan bahwa jalur OJS sangat bergantung pada naikturunnya produksi gula dan kopi di sepanjang jalur rel ini. Dampak yang dirasakan oleh masyarakat akibat dibangunkannya jalur trem Modjoagoeng-Ngoro adalah terbentuknya tempat perdagangan kecil di sekitar stasiun pemberhentian OJS.